Biomass Burning Unlikely to Account for Missing Source of Carbonyl Sulfide. Issue 24 (28th December 2019) - Stinecipher, J.R.; Cameron‐Smith, P.J.; Blake, N.J.; Kuai, L.; Lejeune, B.; Mahieu, E.; Simpson, I.J.; Campbell, J.E.
Abstract: Carbonyl sulfide (OCS) provides a proxy for measuring photosynthesis and is the primary background source of stratospheric aerosols. OCS emissions due to biomass burning are a variable and substantial (over 10%) part of the current OCS budget. OCS emission ratios from open burning fires, coupled with 1997–2016 data from the Global Fire Emissions Database (GFED4), yield OCS biomass burning emissions with a global average annual flux of 60 ± 37 Gg(S) year −1 . A global box model suggests these emissions are more consistent with observations from global atmospheric composition monitoring networks than fluxes derived from previous synthesis papers. Even after considering the uncertainty in emission factor observations for each category of emissions and the interannual variation in total burned dry matter, the total OCS emissions from open burning are insufficient to account for the large imbalance between current estimates of global OCS sources and sinks. Plain Language Summary: Carbonyl sulfide is a naturally occurring gas that can help us understand how much carbon dioxide plants take out of the atmosphere for photosynthesis. In this study we want to understand how much carbonyl sulfide comes from forest fires and other burning, as opposed to other sources. We estimate carbonyl sulfide emissions from fires around the world based on where fires occurred and what was burned then use a computer model to see whether our estimates line up with real‐world measurements of carbonyl sulfide in the atmosphere. We find that fires are a smaller source of carbonyl sulfide than previously reported. Key Points: Bottom‐up estimate of carbonyl sulfide (OCS) emissions from biomass burning is insufficient to close the existing OCS budget gap Long‐term observational records indicate that some previously reported OCS emission factors from peat are not globally representative Biome‐specific emission factors imply a spatial redistribution of emissions relative to previous studies using fixed emission factors